2013
DOI: 10.2486/indhealth.2013-0015
|View full text |Cite
|
Sign up to set email alerts
|

Job Strain, Sleep and Alertness in Shift Working Health Care Professionals —A Field Study

Abstract: Abstract:We explored the associations of job strain with sleep and alertness of shift working female nurses and nursing assistants. Participants (n=95) were recruited from the Finnish Public Sector Study, from hospital wards that belonged to the top or bottom quartiles on job strain. Participants' own job strain was at least as high in high-strain group or low in low-strain group as the ward's average. The study included three-week measurements with sleep diary and actigraphy. Psychomotor Vigilance Test (PVT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 54 publications
(72 reference statements)
5
31
1
Order By: Relevance
“…Davy and Göbel 2013;Ruggiero and Redeker 2013;Bonnefond et al 2001). Very few (4%) nurses in these data (Karhula et al 2013) napped during the night shift. The sleepiness values during the pre-selected, circadian rhythm standardised shifts were similar among the two different work stress groups, indicating that severe sleepiness was not fully congruent with the subjective workload during these shifts.…”
Section: Downloaded By [Mcmaster University] At 05:52 16 March 2015mentioning
confidence: 84%
“…Davy and Göbel 2013;Ruggiero and Redeker 2013;Bonnefond et al 2001). Very few (4%) nurses in these data (Karhula et al 2013) napped during the night shift. The sleepiness values during the pre-selected, circadian rhythm standardised shifts were similar among the two different work stress groups, indicating that severe sleepiness was not fully congruent with the subjective workload during these shifts.…”
Section: Downloaded By [Mcmaster University] At 05:52 16 March 2015mentioning
confidence: 84%
“…1 17-21 Physicians working under acute care conditions, for example, in Emergency Departments (EDs), face a combination of cognitive load, interruptions, communication challenges and time-urgency conditions that are reported to increase the risk of adverse medical events. [22][23][24][25][26][27][28][29][30][31] Of special interest is whether stressor-induced biological processes, such as activation of the hypothalamic-pituitary-adrenal axis and inflammation, contribute to cognitive deficits in physicians. 16 32 33 Consistent with this hypothesis, Rauchenzauner et al demonstrated a positive association between provider on-call duties and inflammatory and cardiac autonomic processes implicated in cardiovascular disease processes, although the impact of professional performance was not determined.…”
Section: Introductionmentioning
confidence: 99%
“…Examining workers in the extended-care setting was of our interest, because their work context may be associated with high job strain, less control over work time, and high work-family conflict, which may have implications for poor sleep. 23 …”
Section: Introductionmentioning
confidence: 99%